2011
DOI: 10.1021/jp209105z
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Process of Peptide Amphiphile Worm-Like Micelles

Abstract: Peptide amphiphile molecules (PA) are remarkably versatile and useful as building blocks for construction of complex supramolecular structures in a bottom-up fashion. Worm-like micelles of PA have been demonstrated to have successful application to creation of synthetic extracellular matrix materials for tissue engineering and regenerative medicine. However, the pathway of the self-assembly process of the PA worm-like micelle has not been fully characterized or understood. This work analyzes the self-assembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 19 publications
(27 reference statements)
6
50
0
Order By: Relevance
“…While PA fibres with high concentration are known to bundle themselves and form close packed hexagonal network36, we demonstrate that water molecules between fibres in these close packed hexagon play a key role in stabilizing this fibre network. Note that the process of micelle formation followed by fibre formation has been reported in previous experimental and simulation studies133738394041. Previously Tirrell et al .…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…While PA fibres with high concentration are known to bundle themselves and form close packed hexagonal network36, we demonstrate that water molecules between fibres in these close packed hexagon play a key role in stabilizing this fibre network. Note that the process of micelle formation followed by fibre formation has been reported in previous experimental and simulation studies133738394041. Previously Tirrell et al .…”
Section: Resultssupporting
confidence: 56%
“…The cryo-TEM images of the C16−W3K solution taken immediately after making the solution showed existence of many discrete spherical micelle structures of around 10 nm diameter39. They also found spherical and shorter ‘worm-like' micelles which suggested that micellar transition occurs through collision of spherical micelles and/or shorter extended micelles; at least during the initial stages40. AFM images by Shimada et al .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…When the peptide was coupled to short alkyl chains (containing 12 or less carbons) no aggregates were formed, whereas with longer tails (containing more than 16 carbons) the PAs formed highly stable assemblies. Tirrell and co‐workers have investigated PA molecules that can self‐assemble into micellar structures . A different PA design, containing a pentapeptide head group based on a sequence from procollagen I attached to a hexadecyl lipid chain (C 16 ‐KT 2 KS) was shown to assemble into extended nanotapes in aqueous solution .…”
Section: Design Of Supramolecular Materialsmentioning
confidence: 99%
“…Phe-Phe, tert-butyl dicarbonate (Boc)-Phe-Phe) 7,8,[16][17][18][19][20][21] . The structures formed by these homoaromatic peptides include tubular structures, spheres, sheet-like assemblies and fibers 6,8,15,[21][22][23][24][25][26][27][28][29][30][31][32] . The fibers in some cases generate a fibril mesh that yields a hydrogel [33][34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%